VD_FINDINFO Pron / 2009 / 72 vom 11. Januar 2010 - VD Tribunal cantonal (2010)
RESTITUTION DU DÉLAI, DÉLAI DE RECOURS, FORCE MAJEURE | 35 CPC, 37 al. 1 CPC, 37 al. 2 CPC, 37 CPC, 458 al. 2 CPC, 464 al. 1 CPC